1996
DOI: 10.1103/physrevb.53.350
|View full text |Cite
|
Sign up to set email alerts
|

Muon-spin-relaxation study of the critical longitudinal spin dynamics in a dipolar Heisenberg ferromagnet

Abstract: Muon-spin-relaxation study of the critical longitudinal spin dynamics in a dipolar Heisenberg ferromagnet Yaouanc, A.; de Reotier, P.D.; Gubbens, P.C.M.; Mulders, A.M.; Kayzel, F.E.; Franse, J.J.M.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
27
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 22 publications
5
27
0
Order By: Relevance
“…One of the systems that has been extensively studied is the intermetallic ferromagnets. For example, GdNi 5 is an axial ferromagnet with a critical temperature of approximately T c ∼31 K [96]. It is characterised by extremely weak magnetic anisotropy arising from the dipole moment interaction between the Gd 3+ .…”
Section: Critical Point Spin Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the systems that has been extensively studied is the intermetallic ferromagnets. For example, GdNi 5 is an axial ferromagnet with a critical temperature of approximately T c ∼31 K [96]. It is characterised by extremely weak magnetic anisotropy arising from the dipole moment interaction between the Gd 3+ .…”
Section: Critical Point Spin Dynamicsmentioning
confidence: 99%
“…It is characterised by extremely weak magnetic anisotropy arising from the dipole moment interaction between the Gd 3+ . ZF muon measurements were performed as a function of temperature on two crystalline samples with different orientations with respect to the muon's initial spin direction (c-axis either parallel or perpendicular to the muon's spin) [96]. It was shown that above T c , the relaxation rate is temperature independent, reflecting the vanishing pair correlations at high temperature, as a result of the relatively low density of states at the Fermi level [97].…”
Section: Critical Point Spin Dynamicsmentioning
confidence: 99%
“…3. We note two features: (i) λ d = 0.029(3) µs −1 is constant below ∼100 K, and (ii) with decreasing temperature there is an unusual step-like increase in λ d below T M but no sign of the paramagnetic-state divergence that is often found in frustrated and unfrustrated magnets [17][18][19][20] due to critical slowing down of dynamic fluctuations. This absence suggests a mean-field-like transition.…”
mentioning
confidence: 99%
“…The two scaling variables at play depend on two material parameters: ξ 0 , the magnetic correlation length at T = 2T C , and q D , the dipolar wave vector which is a measure of the strength of the exchange interaction relative to the dipolar energy. This model initially derived for the paramagnetic phase applies also below T C [16]. Specifically, the model predicts that…”
mentioning
confidence: 99%
“…λ Z (T ) has been computed several years ago [15] for the critical regime of dipolar Heisenberg ferromagnets and has been successfully compared to experiments [15][16][17]. It is based on the derivation of the static and dynamical scaling laws from mode coupling theory [18].…”
mentioning
confidence: 99%